Promoting Environmental Awareness to Underprivileged Children in Jakarta By Holding a Special Event â€œThe Joy of Children 2016â€ - Magdalena Fenisia Caroline; Anastasia Maria Sri Redjeki (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2017)
Lack of awareness to the urgency of environmental issues, especially those related to water pollution, has become one of the reasons among underprivileged children in Jakarta for not conserving the environment because it is not really a matter for them. They are not aware about the correlation between how people affect the water quality and the damages caused to marine environments. To cope with the water pollution issue, it is important to enact educational programs for them so they can be informed of how to conserve water, have proper hygiene, and maintain sanitation. Therefore, the writer created a pilot project focusing on underprivileged children in Jakarta to promote awareness of water pollution by holding a special event â€œThe Joy of Children 2016â€ â€“ Generasi Pelindung Air on 6th and 7th August 2016 at Cakung and Cilincing, areas in the outskirts of Jakarta. It was supported by WWF Indonesia Panda Mobile, SiDalang (Kreasi Daur Ulang), and WatSan Action â€“ Yayasan Tirta Lestari who took part as the educators for the event. By using human-centered approach in special event concept, the writer conducted the workshop at where the problem is, by walking a tour through the community to identify and highlight the problem, to have a discussion, and to play a game with the experts. It was successfully held and the objective of the event was not only achieved for the children participant but also for the committee.